2022
DOI: 10.30773/pi.2021.0147
|View full text |Cite
|
Sign up to set email alerts
|

Serial Multiple Mediation of the Correlation Between Internet Addiction and Depression by Social Support and Sleep Quality of College Students During the COVID-19 Epidemic

Abstract: Objective This cross-sectional study explores the serial multiple mediation of the correlation between internet addiction and depression by social support and sleep quality of college students during the COVID-19 epidemic.Methods We enrolled 2,688 students from a certain university in Wuhu, China. Questionnaire measures of internet addiction, social support, sleep quality, depression and background characteristics were obtained.Results The prevalence of depression, among 2,688 college students (median age [IQR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
2
18
1
Order By: Relevance
“…In this context, problematic Internet use may be a predictor in screening high-risk students for mental health problems ( 30 ). Jiang et al ( 27 ) also revealed that internet addiction was directly related to college students' depression and indirectly predicted students' depression via the mediator of social support and sleep quality. On the other hand, under the mediation of fear of missing out, young people with anxiety are more likely to develop Internet gaming disorder, while young people with depression or stress may be susceptible to other types of Internet use disorders ( 99 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this context, problematic Internet use may be a predictor in screening high-risk students for mental health problems ( 30 ). Jiang et al ( 27 ) also revealed that internet addiction was directly related to college students' depression and indirectly predicted students' depression via the mediator of social support and sleep quality. On the other hand, under the mediation of fear of missing out, young people with anxiety are more likely to develop Internet gaming disorder, while young people with depression or stress may be susceptible to other types of Internet use disorders ( 99 ).…”
Section: Discussionmentioning
confidence: 99%
“…The co-occurrence of Internet addiction and anxiety symptoms, depressive symptoms, and stress in students suggests that Internet addiction is positively associated with other mental health problems ( 41 ). The results could be explained by the ongoing pandemic and by the fact that excessive use of the Internet impairs psychological wellbeing, which can be a driver of psychological distress ( 27 31 ). Particularly in the context of the COVID-19 pandemic, the Internet has been used as an effective tool to provide distance education.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations